2022
DOI: 10.7324/japs.2022.120917
|View full text |Cite
|
Sign up to set email alerts
|

First-generation antipsychotics use and reduced risk of pneumonia—Clinical implications in SARS-CoV2 treatment: A systematic review and meta-analysis of observational studies

Abstract: The use of antipsychotics (AP) has been linked to nearly 60% increase in the incidence of pneumonia. The study purposes to devise safest treatment regimens for psychiatric patients with underlying respiratory comorbidities. A systematic literature search was conducted. A total of 41 studies were evaluated, which included 33 articles for metaanalysis. The quality of retrieved articles was screened by reviewing independently. The risk of bias in each study was assessed using the Newcastle-Ottawa Scale. Inter-rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…23,24 Our previously published article on the systematic review and meta-analysis studying the effect of antipsychotics on respiratory function provide the evidence that FGAs are particularly associated with a lower risk for pneumonia compared to exposure to other psychotropics drugs, whereas SGAs are more significantly associated with the development of pneumonia. 25 Studies have reported the increased risk of respiratory illness, including pneumonia and respiratory failure following Benzodiazepine (BZD) usage. The current and recent past use of BZD is related to a higher chance of pneumonia occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Our previously published article on the systematic review and meta-analysis studying the effect of antipsychotics on respiratory function provide the evidence that FGAs are particularly associated with a lower risk for pneumonia compared to exposure to other psychotropics drugs, whereas SGAs are more significantly associated with the development of pneumonia. 25 Studies have reported the increased risk of respiratory illness, including pneumonia and respiratory failure following Benzodiazepine (BZD) usage. The current and recent past use of BZD is related to a higher chance of pneumonia occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Our previously published article on the systematic review and metaanalysis studying the effect of antipsychotics on respiratory function provide the evidence that FGAs are particularly associated with a lower risk for pneumonia compared to exposure to other psychotropics drugs, whereas SGAs are more signi cantly associated with the development of pneumonia. 25 Studies have reported the increased risk of respiratory illness, including pneumonia and respiratory failure following benzodiazepine (BZD) usage. The current and recent past use of BZD is related to a higher chance of pneumonia occurrence.…”
mentioning
confidence: 99%